Heavy metals accumulation in house crow (Corvus splendens Vieillot) in Klang, Selangor, Malaysia - Al-Janaydeh, Mohammed Ali Ahmed (2021)
Heavy metals have become a major concern to the world due to its transferability through the food chain, and eventual bioaccumulation in animals and human beings. There are indications that exposure to these heavy metal pollutants could cause death and other serious health risks in men and women such as in study areas. In particular, kidney infections, urinary tract, uterus, diabetes and rental infection in men and women are common cases, which can be directly linked with excessive toxicity of high concentration from heavy metals contamination. This study explores the potential of Caspase-3 and antioxidant enzymes as biomarkers for assessing heavy metals in house crows (Corvus splendens). Specifically, the objectives of this study were: 1) to determine the accumulation of heavy metals in house crow in order to evaluate the status of heavy metal pollution in the Klang area. 2) to evaluate the relationship between heavy metals accumulation and antioxidant status of SOD activity, Cp ferroxidase activity and GSH concentration in house crow from Klang area. 3) to determine the relationship between heavy metals accumulation and apoptosis marker and HSP70 overexpression in house crow tissues especially in liver and kidney tissues. House crow samples were collected from the Klang area through the Department of Public Health, Klang Municipal Council. Quantitative determination of heavy metals (Cu, Zn, Ni, Fe, Cd and Pb) was carried out using atomic absorption spectrophotometer (AAS). In addition, standard procedures were for evaluating the liver and kidney function profile, antioxidant enzyme activities in plasma blood and tissues have been determined using colorimetric kits. Immunohistochemistry protocol for liver and kidney tissues were performed by using Caspase-3 and HSP70 monoclonal antibodies. Results show that heavy metals were accumulated in all body parts and organs of house crows tested. Fe concentrations were the highest, followed by those of Zn, Cu, Pb, Ni and Cd. Feathers, bone and kidney accumulated high concentrations of Pb and Cd whereas liver accumulated high concentrations of essential heavy metals (Fe>Zn>Cu>Ni). This study revealed positive and significant correlation (r= 0.405, P<0.05) between gizzard content (food) metals accumulation and internal organ’s heavy metals of house crow for heavy metals such as Pb, Cd, Ni, and Fe. Significant variations in the SOD activities among adult and juvenile and/or male and female crow samples were also detected in liver and kidney tissues. SOD activity was observed to be age and/or sex-dependent in liver and kidney organs while Cp ferroxidase activity was also age and/or sex-dependent in plasma of the house crows. In addition, Caspase-3 and HSP70 marker results were age and/or sex-dependent in liver tissues while Caspase-3 results was age and/or sex-dependent only in kidney tissues of the house crows. Statistically, the adult female house crow had the highest concentration of heavy metals in the liver than the male and juvenile house crows. Furthermore, the adult male house crows had the highest concentrations of heavy metals in the kidney than the female and juvenile house crows. The findings of the present study indicated that non-essential heavy metal was bioaccumulated at a significantly lower rate in the liver compared to bioaccumulation in other body organs as a result of liver detoxifications. Analysis of non-essential and essential heavy metals in house crows’ body tissues in this study allows assessing environmental pollution of heavy metals in the bird and their environment. Bioaccumulation of metals in internal body organs is reflection of chronic exposure, which is dependent on contaminant level in food ingested, because liver and kidney are sites of detoxification while muscle, brain, bone and heart are sites of accumulation. Moreover, lung tissues and feathers are sites of exposure and excretion. Accumulation of heavy metals in breast feathers and lungs reflect the presence of pollutants in the environment. The breast feathers could be utilized as a detector of heavy metals in house crows, to evaluate quantitatively the concentrations of heavy metals in breast feathers related to the internal organs such as liver and kidney. More importantly, this study reveals the suitability of breast feathers, as an alternative sample to internal organs, in studying heavy metals accumulation in house crow. The results from this study show that, contamination of heavy metals contamination has various effects on the antioxidant biomarker levels in the blood and tissues (liver and kidney) of house crow in peninsular Malaysia. Adult and female house crows showed reduced Cp ferroxidase activity, which can be associated with increased heavy metal concentration (Pb, Cd, Zn and Ni). However, the Pb exposed house crows showed decreased Cp ferroxidase activity with increasing Pb concentration while the Pb and Cd exposed house crows showed decreased SOD activity with increased Pb and Cd concentration in liver and kidney tissues. Additionally, Caspase-3 immunoreactivity in this study was concentration dependent; the higher Pb and Cd concentration in the liver or kidney, the higher the reactivity of Caspase-3. The present study clearly shows the utility of Caspase-3, SOD activity and Cp ferroxidase activity, especially in the house crow as suitable biomarkers for oxidative stress of Cd and Pb metals in the Klang area. The implication of this study on the Malaysian environment policy is the need for a review as to mitigate the presence of heavy metals in the environment, which are capable to cause severe harm to human population. Again, there is a need to strengthen the policy and it is compliance in order to reduce activities that cause high level of heavy metal pollutions in the environment such as highly usage of chemicals in agriculture.